Analisis Semiotika Puisi “Hatiku Selembar Daun” Karya Sapardi Djoko Damono (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Poetry is one type of literary work that has the deepest literary statement. The words that are raised contain deep understanding and are full of symbols. Reading poetry is a pleasure of literary art because the reader is brought along into the statements that a poet pours out through the lines of his poem. In the Big Dictionary Indonesian it is stated that poetry is a variety of literature whose language is bound by rhythm, matra, rhyme, and the arrangement of arrays and couplets.1Rahmat Djoko Pradopo gives the definition of poetry as a bound essay. The limitations of the poem are based on the attachment to (1) Many lines in each stanza, (2) Many words in each line, (3) Many syllables in each line, (4) Rhyme, and (5) Rhythm. Researchers are interested in conducting research on analyzing a poem by Sapardi Djoko Damono entitled